(untitled) (Journal of Hama University, 2022)
Recently, interest has focused on preserving the dental pulp as much as possible through Vital Pulp Therapeutique Techniques , which rely on maintaining the vitality and function of the pulp tissue in vital permanent teeth. This research aims to explore the opinions and behavior of general practitioners and Endodontists in Syria regarding vital pulpotomy in permanent teeth, and the materials used in this Procedure. The sample consisted 472 endodontists and general practitioner dentists in Syria. The questionnaire consisted of 7 questions about coronal pulpotomy in permanent teeth. The results showed that 73.6% of the participants had prior knowledge of the coronal pulpotomy procedure. 69% of the participants had performed a pulpotomy MTA was the most widely used substance by the participants with a percentage of 37%, and the main reason for 89.2% that prompted practitioners to perform a coronal pulpotomy was pulp exposures that were not accompanied by symptoms of spontaneous pain. Most of the participants promised this procedure a phased procedure by 73%, and the greatest fear was necrotizing The remaining pulp after pulpotomy 72% The data was analyzed after being collected from the participants using chi-square analysis at a significance level of 0.05 .